2010
DOI: 10.1007/s10144-010-0198-5
|View full text |Cite
|
Sign up to set email alerts
|

Predation as a probable mechanism relating winter weather to population dynamics in a North American porcupine population

Abstract: An abundance index of an eastern Quebec population of North American porcupines (Erethizon dorsatum) has cycled with superimposed periodicities of 11 and 22 years from 1868 to 2000. This cycle closely followed 11-and 22-year cycles in solar irradiance and local weather (e.g., winter precipitation and spring temperature), generating the hypothesis that solar activity may affect porcupine abundance through effects on local weather. We investigated the mechanisms linking porcupine abundance to local weather condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Although, porcupines in the Great Basin Desert experienced nutritional limitation during winter, the relatively more moderate winter conditions likely exerted only a weak influence on survivorship. Our findings are corroborated by those from an analogous system with similar climatic patterns; Mabille et al (2010) found that winter precipitation modulated predatory influence on a porcupine population in southern Canada by altering snow conditions, which drove adult survivorship.…”
Section: Discussionsupporting
confidence: 86%
“…Although, porcupines in the Great Basin Desert experienced nutritional limitation during winter, the relatively more moderate winter conditions likely exerted only a weak influence on survivorship. Our findings are corroborated by those from an analogous system with similar climatic patterns; Mabille et al (2010) found that winter precipitation modulated predatory influence on a porcupine population in southern Canada by altering snow conditions, which drove adult survivorship.…”
Section: Discussionsupporting
confidence: 86%
“…While previous studies have usually dealt with determining the effect of climatic conditions on habitat selection (Dussault et al 2005, Hansen et al 2010, Stahlschmidt et al 2011 or, directly, on vulnerability to be predated (Stenseth et al 2004, Wikenros et al 2009, Mabille et al 2010, our approach allowed us to get a better insight into the behavioral mechanism indirectly linking environmental drivers to predation risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, predator avoidance may also lead animals to reduce their activities (Lima & Dill, 1990). Porcupines suffered high predation rates from fishers (Martes pennanti) during our study, and predation was linked to snow cover (Mabille, Descamps & Berteaux, 2010), probably because porcupines have short limbs and are thus vulnerable to predators when there is snow. In fact, porcupines spent less time outside of the den and had shorter activity bouts when snow penetrability was high, which may represent behavioural responses to increased predation risk.…”
Section: Duration Of Activity Bouts (H)mentioning
confidence: 98%
“…Thermal conditions measured with T ref ( fragmented by abandoned and cultivated fields and characterized by a rugged topography, abundance of natural rock dens, and a mixed-boreal forest. The study population has been monitored each summer since 2000 and sometimes reached a high density (Mabille, Descamps & Berteaux, 2010). The population was at medium density and comprised about 40 individually marked porcupines in winter 2004 (see Berteaux, Klvana & Trudeau, 2005 for details on individual monitoring).…”
Section: Study Area and Study Populationmentioning
confidence: 99%